DEVELOPING FINE MOTOR SKILLS USING THE EXPLICIT INSTRCUTION MODEL AND ASSIGNING TASKS IN CUTTING OUT GROUP B PATTERNS IN BAITUL MAKMUR ISLAMIC KINDERGARTEN BANJARMASIN - gina faudina; Novitawati Novitawati (Pendidikan Guru Pendidikan Anak Usia Dini (PG PAUD) Universitas Lambung Mangkurat, 2022)
AbstractThe purpose of this study was to determine the activities of educators, students and the results of children's development in cutting patterns. This study uses a qualitative approach with the type of Classroom Action Research (CAR) conducted in 3 meetings. The research subjects were group B of Baitul Makmur Integrated Islamic Kindergarten with 13 children. The use of the instrument is the activity sheet of educators, students, and developmental results. While the data analysis used descriptive analysis. The findings showed that teacher activity increased from meeting 1 with the criteria of